Molecular Characterization of HBV Strains Circulating among the Treatment-Naive HIV/HBV Co-Infected Patients of Eastern India - Saha, Debraj; Pal, Ananya; Biswas, Avik; Panigrahi, Rajesh; Sarkar, Neelakshi; Das, Dipanwita; Sarkar, Jayeeta; Guha, Subhasish Kamal; Saha, Bibhuti; Chakrabarti, Sekhar; Chakravarty, Runu (PloS one, 2014)
Previously we reported that the exposure to hepatitis B virus (HBV) infection serves as a major threat among the treatment naive HIV infected population of eastern India. Hence, molecular characterization of these strains is of utmost importance in order to identify clinically significant HBV mutations. A total of 85 treatment naive HIV/HBV co-infected participants were included of whom the complete basal core promoter/precore region, the core and the whole envelope gene could be successfully sequenced for 59, 57 and 39 isolates respectively. Following phylogenetic analysis, it was found that HBV/D was the predominant genotype with HBV/D2 (38.5%) being the most prevalent subgenotype followed by HBV/A1. The major mutations affecting HBeAg expression includes the A1762T/G1764A (13.6%), G1896A (22%) and G1862T mutation (33.9%) which was predominantly associated with HBV/A1. Moreover, the prevalence of G1896A was considerably high among the HBeAg negative HIV/HBV co-infected subjects compared to HBV mono-infection. The main amino acid substitutions within the MHC class II restricted T-cell epitope of HBcAg includes the T12S (15.8%) and T67N (12.3%) mutation and the V27I (10.5%) mutation in the MHC class I restricted T-cell epitope. PreS1/S2 deletion was detected in 3 isolates with all harboring the BCP double mutation. Furthermore, the frequently occurring mutations in the major hydrophilic loop of the S gene include the T125M, A128V and M133I/L. Therefore, this study is the first from India to report useful information on the molecular heterogeneity of the HBV strains circulating among the treatment naive HIV/HBV co-infected population and is thus clinically relevant.